Comparison of Retzius-sparing versus anterior robotic-assisted radical prostatectomy in patients with prior transurethral resection of the prostate (TURP) - Schütz, Viktoria; Hatiboglu, Gencay; Würkner, David; Tekesin, Mete; Feißt, Manuel; Duensing, Stefan; Huber, Johannes; Hohenfellner, Markus; Kaufmann, Basil Paul (World journal of urology, 2025)
Background/objectives: Radical prostatectomy (RP) following previous transurethral resection of the prostate (TURP) is technically challenging due to an altered anatomy and fibrosis, often resulting in impaired functional outcomes. Open and anterior robotic approaches (aRARP) were evaluated in this setting, while data on Retzius-sparing robotic radical prostatectomy (rsRARP) is lacking. We aim to compare urinary continence, complications, and oncologic control between rsRARP and aRARP in patients with prior TURP. Patients and methods: A total of 65 patients with localized prostate cancer undergoing rsRARP or aRARP between 2010 and 2022 following prior TURP were analyzed. The primary endpoint was urinary continence recovery (max. one safety pad per day), immediately after catheter removal and at 12 and 24 months. Secondary endpoints included peri- and postoperative complications and biochemical recurrence (BCR)-free survival. Results: Of the included patients, 30 patients (46%) and 35 patients (54%) underwent rsRARP and aRARP, respectively. Median time between TURP and RP was 65 months (IQR 19–132). Immediate continence rate was 73.3% (n = 22) in rsRARP patients vs. 57.1% (n = 20) in aRARP patients. At 12 months, continence rates were 86.2% (rsRARP) vs. 91.2% (aRARP), and at 24 months, 80.8% vs. 93.9%, respectively. The surgical technique was not significantly associated with 12-month continence recovery, while nerve-sparing showed a trend towards improved outcomes. Complications occurred in 15.4% (n = 10), the highest being a grade IIIb according to the Clavien-Dindo classification. At 24 months, BCR-free survival was 89% (95% CI: 79–100) for rsRARP and 97% (92–100) for aRARP (p = 0.42). Conclusion: In patients with prior TURP, RARP using a Retzius-sparing approach is feasible and safe. While long-term continence outcomes are comparable to aRARP, rsRARP may offer improved immediate continence recovery, likely due to superior preservation of anatomical structures relevant to urinary function. These findings support the use of rsRARP even in surgically challenging post-TURP anatomy.
Online veröffentlicht: 05. Dezember 2025
Gesehen am 25.02.2026